Cushioning Effects of Insole and Built-up Heel Materials on Shock Absorption at Heel Strike - TANAKA, Shoichi; HACHISUKA, Kenji; OHMINE, Saburo; SHITAMA, Hideo; OGATA, Hajime (Rihabiritēshon igaku, 1994)
The purpose of this study consisting of material tests, combined material tests and subject tests was to determine which insole and built-up heel materials contributed most to shock absorption at heel strike. During the material tests, we measured the cushioning property of 5, 10, 15, and 20mm thick cork, EVA, felt, natural leather, non bound rubber, PE-lite, rubber sole (SBR), silicon rubber, soft leather, Sorbothane, and sponge rubber by dropping a shot onto each material. Five mm thick Sorbothane or silicon rubber as an insole material and 20mm thick cork, SBR, or EVA as a built-up heel material were excellent as shock absorbing materials. During the combined material tests, 20mm thick cork as a built-up heel material and 5mm thick Sorbothane or sponge rubber as an insole material, and 20mm thick EVA and 5mm thick Sorbothane or sponge rubber were found to be effective. During the subject tests the vertical force impact peaks per weight (VFIP) induced by human drop were measured on a Kistler force platform. We tested 6 subjects who wore an Oxford shoe with each combination of an insole material: 5mm thick Sorbothane, silicon rubber or sponge rubber and a built-up heel material: 20mm thick EVA, cork or natural leather. VFIPs of the combinations of natural leather and insole materials were significantly smaller than those of the combinations of EVA or cork and insole materials. As the results of the subject tests were not consistent with those of the combined material tests, an additional human drop test at which a subject wore an Oxford shoe with a fixed ankle joint was performed. The additional test revealed that VFIPs of EVA was smaller than those of natural leather. We, therefore, concluded that an ankle joint compensatory movement induced a shock absorbing function in the case of a natural leather heel at heel strike and that shock absorbing materials should be prescribed for shoes if a patient has an ankle joint disorder and limited range of motion. We propose that the best standard prescription of shock absorbing materials is 5mm sponge rubber as an insole material and 20mm EVA as a built-up heel material. It is important to consider the cushioning properties of insole and built-up heel materials for patients with ankle joint disorders at heel strike.